ANALISIS TOKSISITAS EKSTRAK BUAH PINANG YAKI (Areca vestiaria Giseke) - Kamu, Vanda (Sam Ratulangi University, 2010)
ABSTRACTKamu et al., 2010. Toxicity analysis of pinang yaki (Areca vestiaria Giseke) fruit extract.A research had been conducted to determine the toxicity of pinang yaki fruit extract. Toxicity analysis was done using BSLT (Brine Shrimp Lethality Test) method. Pinang yaki were divided into two treatment namely seed and skin using ethanol and petroleum ether as solvents. The result shows that pinang yaki extract were toxic with LC50 value are 225,652 ppm for ethanol extract (seed), 213,296 ppm for ethanol extract (skin) and 1,547 ppm in petroleum ether extract (seed).Keywords : toxicity, LC50, pinang yaki